Pencegahan Stunting di Kabupaten Jember Melalui Pelatihan Pembuatan “TOLE” Pentol Lele di Desa Kemuning Lor - Putra, Dony Setiawan Hendyca; Roziqin, Mochammad Choirur; Rindiani, Rindiani; Warsito, Heri; Ananda, Nadiva Dwi; Amanda, Maharani; Subandi, Lintar Buana (SEJAGAT : Jurnal Pengabdian Masyarakat, 2025)
Stunting in Jember Regency is among the top five in East Java. Kemuning Lor Village is one of the villages that needs attention in stunting prevention. Knowledge about stunting prevention is very much needed by all layers of society. Regional potential also supports the success of stunting prevention. The majority of the residents' jobs there are as livestock farmers. This greatly supports the proposing team in implementing Sustainable Empowerment of representative Through Training in the Production and Digital Marketing of Pentol Lele as an Effort to Prevent the Increase of Stunting Cases in Jember Regency by providing socialization and training as well as direct practice in the processing of Pentol Lele. The purpose of this community service is to provide training in the production and digital marketing of Pentol Lele as an effort to prevent the increase in stunting cases in Jember Regency. The nutritional content of catfish is comparable to other fish, even though it is relatively cheaper. The results of this activity are: 1) Increased public knowledge about early stunting prevention; 2) Increased public knowledge about making catfish meatballs; 3) Increased public knowledge about marketing UMKM products through digital marketing training; 4) Enhanced public knowledge about how to manage P-IRT. This community empowerment activity is monitored and evaluated in stages to optimize stunting prevention and the sustainability of UMKM products, and to improve the economy of the Kemuning Lor Village.